Implementation of the SAW Method on the Employee Career Determination Website at PT. Hartono Palace of Technology - Christian Davin Santoso; Rudi Sutomo (Universitas Islam Raden Rahmat, Malang, 2023)
PT. Hartono Istana Teknologi is a company in Indonesia engaged in electronics and there are obstacles encountered including evaluating employee performance and determining employees entitled to promotion using data in the form of paper stored separately and Excel files for data collection on employee performance assessments that have not been integrated such as data agreements, training data from company and achievement data are not yet systematic so companies need an integrated information system for employee career path processes. Based on the problems above and the research is focused on website-based implementation to provide solutions to companies for career path problems in companies that can increase work effectiveness and automate the eligibility criteria process for promotion. In the process of making a website, one of the features of the Decision Support System (DSS) is used, namely the Simple Additive Weighting (SAW) method. Blackbox testing has been carried out with an average result of 77.5% indicating the success of the application feasibility test for implementation at PT Hartono Palace of Technology